Endo-restorative management of a type II dens invaginatus in mandibular premolar associated with a large cyst - Swati Borkar; Anita Dhupar; Manjita Parab (Wolters Kluwer Medknow Publications, 2017)
We present the management of a case of Type II dens invaginatus in a mandibular premolar with a large invagination in the coronal third of the root on mesial aspect of the crown in proximity of cementoenamel junction significantly compromising the strength of the crown structure. We describe in detail the various measures taken to assess the internal tooth structure destruction and enhance the fracture resistance of the involved premolar. The case has a long-term follow-up of 36 months showing clinical and radiographic signs of healing. We highlight use of a simple "foil coated fiber postblocker technique" for root reinforcement in the first premolar. Successful management of teeth with dens invaginatus can be effectively done using with careful treatment planning and selection of reinforcing adhesive restorative materials.